The fucoidan from sea cucumber Apostichopus japonicus attenuates lipopolysaccharide-challenged liver injury in C57BL/6J mice. (October 2019) - Yin, Jiayu; Yang, Xiaoqian; Xia, Bin; Yang, Zixun; Wang, Ziwei; Wang, Jin; Li, Ting; Lin, Ping; Song, Xiaotong; Guo, Shoudong
Graphical abstract: Highlights: Fucoidan was prepared from A. japonicus and evaluated in LPS-challenged mice. This fucoidan reduced expression of pro-inflammatory factor: TNF-α, IL-1β and IL-6. This fucoidan reduced the expression of iNOS, and inactivated MAPK/NF-κb pathway. This fucoidan suppressed the AKT/mTOR pathway by inhibition of phosphorylation. Abstract: Sea cucumber is a functional food in Asia countries. This study was designed to investigate whether the fucoidan from sea cucumber A. japonicus has an anti-inflammatory effect in the liver of lipopolysaccharide (LPS)-challenged mice. Our results demonstrated for the first time that the fucoidan reduced the pathologic changes and levels of pro-inflammatory cytokines, such as, TNF-α, IL-1β and IL-6. RT-PCR and western blot results demonstrated that this fucoidan significantly reduced the expression of iNOS and the phosphorylation of NF-κB P65, P38 and ERK1/2, but not JNK compared to the model group. Furthermore, this fucoidan significantly suppressed the phosphorylation of AKT, mTOR, p70S6K, RPS6 and GSK3β, but not GSK3α. These results demonstrated this fucoidan has a powerful anti-inflammatory effect in the liver of LPS-challenged mice via down-regulating MAPK/NF-κB and AKT/mTOR pathways, and the expression of iNOS. Collectively, food intake of sea cucumber may have a potential effect against inflammation.